Analisis Kepemimpinan terhadap Kinerja Guru di SMP Muhammadiyah 10 Yogyakarta - Afani, Adinnda Noor; Marampa, Adriana Madya; Santi, Winda Noor (Journal of Comprehensive Science, 2025)
This study aims to analyze the leadership style of the principal at SMP Muhammadiyah 10 Yogyakarta and its impact on teacher performance. Using a descriptive qualitative approach, data were collected through observations, in-depth interviews, and document studies. The findings indicate that the principal applies a transformational and collaborative leadership style, characterized by openness, support for innovation, and the empowerment of teachers. Strategies such as continuous academic supervision, internal training, the establishment of learning communities, and the use of educational technology have proven to positively affect teacher motivation, professionalism, and work spirit. However, challenges such as the digital literacy gap, high administrative burdens, and varying teacher characteristics remain significant obstacles. These findings highlight the importance of adaptive, communicative leadership that fosters collaboration in creating a productive work environment and enhancing the quality of education. This study is expected to contribute to the development of leadership in schools and provide insights for school principals in utilizing effective leadership strategies to improve teacher performance.